Kematangan Emosi dan KontrolDiri dengan Kenakalan Remaja - Febrianti, Kartika Ulfa; Indrawati, Erdina (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Juvenile delinquency is an act that violates the law and makes the child become naughty.Juvenile delinquency can be avoided if you have good emotional maturity and self-control.This study aims to determine emotionalmaturity and self-controlwith juvenile delinquency. Thisresearchis a quantitative research. The research population was 180 students of SMPN 1Batam. The sampling technique uses convenience sampling. Measuring tools used in this studyare the emotionalmaturity scale, self-control scale and juvenile delinquency scale. The dataanalysis techniques usedto test the hypothesis are Bivariate Correlation and MultivariateCorrelation. The results showed that there was a relationship between emotional maturity andjuvenile delinquency with a value of R = -324 and p = <0.000, and there was a relationshipbetween self-control and juvenile delinquencyof R = -274 and p = <0.000, and there was arelationship between emotional maturity and juvenile delinquency. self and juveniledelinquency R = 0.354, R Square 0.125 and p = 0.000 (p <0.05). Simultaneously giving aneffective contribution of 12.5% against juvenile delinquency. Emotional maturity contributes10.5% with (RÂ²) of 0.105 to juvenile delinquency. Meanwhile, self control is 2%with (RÂ²)0,020%. Based on these findings it can be concluded that there is a relationship betweenemotional maturity and self-control with juvenile delinquency at SMPN 1 Batam.